Influences of adversity across the lifespan on respiratory sinus arrhythmia during pregnancy. Issue 6 (30th May 2021) - Kaliush, Parisa R.; Terrell, Sarah; Vlisides‐Henry, Robert D.; Lin, Betty; Neff, Dylan; Shakiba, Nila; Conradt, Elisabeth; Crowell, Sheila E.
Abstract: There is limited understanding of factors across the lifespan that influence pregnant women's respiratory sinus arrhythmia (RSA), which could have implications for their health and offspring development. We examined associations among 162 English‐ and Spanish‐speaking pregnant women's childhood maltreatment history, emotion dysregulation, recent life stress, and resting RSA during the third trimester. Moderated mediation analyses indicated that more severe childhood maltreatment history (95% confidence interval (CI) [0.26, 0.63]) and higher emotion dysregulation (95% CI [0.001, 0.006]) predicted more stress during pregnancy, and childhood maltreatment history interacted with emotion dysregulation to predict resting RSA (95% CI [−0.04, −0.0003]). Exploratory analyses revealed that women's health‐related stress during pregnancy mediated the relation between emotion dysregulation and RSA regardless of childhood maltreatment severity (95% CI [−0.007, −0.002]). These findings suggest that women's resting RSA during pregnancy may reflect physical and emotional stress accumulation across the lifespan and that relations between early life adversity and prenatal psychophysiology may be buffered by protective factors, such as emotion regulation. In addition, these findings underscore the importance of distinguishing between types of prenatal stress. Given the implications for women's health and offspring development, we urge researchers to continue exploring factors associated with pregnant women's psychophysiology.